Ejecución Presupuestaria de los Proyectos Sociales del Gobierno Autónomo Descentralizado Parroquial Rural La Esmeralda - López Haro, Cinthya Tamara (2019)
The present case study was conducted in the GADPR La Esmeralda, belonging to the canton of Montalvo, Province of Los Ríos, which has approximately 11,430 inhabitants, prior to obtaining the degree in Accounting and Auditing, on the subject "Budget execution of the social projects of the Autonomous Decentralized Parochial Rural Government La Esmeralda ", the same that is framed in the sub-line of investigation Financial Management and Social Commitment.